On two species of the spider genus Sphecozone O.P.-Cambridge and a case of hermaphroditism in Sphecozone personata (Simon, 1864) (Araneae: Linyphiidae) - Rodrigues, Everton Nei Lopes; Ott, Ricardo; de S. Mendonça, Milton (Zootaxa, 2012)
Sphecozone O.P.-Cambridge, 1870 includes small to median spiders with 1.4–4.2 mm body size. Known exclusively from the Americas, 34 species are recognized, 14 of them are present in Brazil (Platnick 2011). The female of S. rostrata Millidge, 1991 is described and illustrated for the first time. The male of S. rostrata and both sexes of S. personata (Simon, 1864) are redescribed. New illustrations are presented together with seasonality abundance data for both species. We also provided illustrations of a bilateral hermaphrodite specimen of S. personata.